Proposal for municipalities and local governments pavement management systems - Sotil Chávez, Andrés (2014)
The following paper provides a proposal for a Pavement Management System for municipalities and/or local government with low funds, and from which a further sophistication can take place.The paper has the main objective of proposing to the respective jurisdictions a methodology that allows abandon the maintenance practices based on politics (local pressures, claims), to convert it into a more objective, rationalized and programmed probabilistic/stochastic methodology, based on serviceability and functional evaluations.Once the PMS is established, it is proposed that the jurisdictions start building a historic database so that they can jump towards an empiric methodology of their own, that eventually will allow the future implementation of mechanistic-empiric methodologies.This paper provides an applicative example that can be used as an example by other jurisdictions. Even more, it can be taken as the starting point for the preparation and later implementation of a national manual for the country’s PMS.